2019
DOI: 10.1210/js.2018-00287
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hashimoto Thyroiditis on the Development of Thyroid Nodules and Cancer in Children and Adolescents

Abstract: It is unclear whether patients with Hashimoto thyroiditis (HT) are predisposed to develop thyroid nodules and/or thyroid cancer. The objective of our study was therefore to assess the prevalence of thyroid nodules and/or cancer in patients with HT and to look for possible prognostic factors. A retrospective survey of 904 children/adolescents with HT (709 females, 195 males) regularly followed in nine Italian centers of pediatric endocrinology was performed. Median period of follow-up was 4.5 years (1.2 to 12.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 44 publications
(39 reference statements)
4
31
1
Order By: Relevance
“…All the six studies included in the final analysis were retrospective. The 11 studies included a total number of 2,065 patients with HT, with individual study cohorts counting from 89 to 904 children [20][21][22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the six studies included in the final analysis were retrospective. The 11 studies included a total number of 2,065 patients with HT, with individual study cohorts counting from 89 to 904 children [20][21][22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…The severity of hypoechogenity at ultrasound, anti-TPO antibodies and free T4 serum concentrations were predictive for the appearance of new nodules. Radetti et al concluded that HT seems to influence the development of thyroid nodules, but not cancer in children and adolescents [25].…”
Section: Resultsmentioning
confidence: 99%
“…Well-differentiated thyroid cancers are the most common endocrine tumors in children and adolescents. A significant increase in the incidence of thyroid cancers was observed in children following the nuclear reactor meltdown in Ukraine and those exposed to the atomic blasts in Japan [5,6].…”
Section: Resultsmentioning
confidence: 99%
“…1). In other pediatric multicenter cohort, involving children and adolescents affected by HT, a very low prevalence of TC (1.1%) compared to other series has been reported [21]; these author did not demonstrate influence of TSH levels on TC occurrence, likely due to the small number of patients with TC in their cohort [21]. Furthermore, Kambalapalli et al [22] reported a 4% of prevalence of TC in a group of children and adolescents with goiter without statistical difference between positive and negative thyroid peroxidase antibody (TPOAb) patients.
Fig.
…”
Section: Introductionmentioning
confidence: 95%
“…Although an increased risk of TC in children and adolescents with nodular HT is still debated and not constantly reported [8, 21], it seems likely that increased levels of TSH, a consequence of the thyroid damage by the autoimmune process, could be a factor of risk of TC.…”
Section: Introductionmentioning
confidence: 99%